1999
DOI: 10.1021/ja983878n
|View full text |Cite
|
Sign up to set email alerts
|

The Solvation of Acetonitrile

Abstract: Acetonitrile is an extremely important solvent and cosolvent. Despite this, we have no general picture of the nature of mixed liquids containing acetonitrile applicable across-solvent families. We consider the properties of acetonitrile dissolved in 33 solvents, focusing on interpretation of the environment-sensitive solvent shift, Δν, of its CN stretch frequency, ν2. The two major models (dispersive and specific solvation) which have been proposed to interpret Δν are based on diverse experiments with incompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
331
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(365 citation statements)
references
References 92 publications
30
331
2
Order By: Relevance
“…Similar shifts of the peak position were reported for the SFG spectrum of CH 3 symmetric stretching mode at the vapor/water-methanol mixture [19,33] or at the vapor/water-acetone mixture interface [20]. It is well accepted that the stretching frequency depends on the electron density localized in the CN bond, which suggests that higher electron density generally weakens the CN bond strength [17,34]. As a consequence, the vibrational frequency becomes red-shifted.…”
Section: Resultssupporting
confidence: 74%
“…Similar shifts of the peak position were reported for the SFG spectrum of CH 3 symmetric stretching mode at the vapor/water-methanol mixture [19,33] or at the vapor/water-acetone mixture interface [20]. It is well accepted that the stretching frequency depends on the electron density localized in the CN bond, which suggests that higher electron density generally weakens the CN bond strength [17,34]. As a consequence, the vibrational frequency becomes red-shifted.…”
Section: Resultssupporting
confidence: 74%
“…The corresponding experiment would be difficult with the hALR2/1/NADP + complex because of the relatively smaller Stark tuning rate and absorptivity of the nitrile. Previous theoretical analysis of vibrational spectroscopy of acetonitrile dissolved in alcohol solvents has shown that, when the CtN group's nitrogen atom acts as a hydrogen bond acceptor, the absorption energy of the CtN bond is perturbed independently of electrostatic effects (48). The proximity of the CtN bond of inhibitor 1 to the hydroxyl group of T113 (modeled at <2 Å for the N‚‚‚O distance, Figure 3) is therefore a possible complication for measuring electrostatic fields in this region of hALR2 with a nitrile probe.…”
Section: Resultsmentioning
confidence: 99%
“…The common, linear electric field sensitivity of the IR and NMR observables leads to a correlation between them in the absence of specific interactions with the probe. Direct hydrogen bond formation to a nitrile leads to a departure from this linear correlation, ascribed to anomalous behavior in the IR but not the NMR dimension (41)(42)(43). By comparing tandem IR and NMR measurements for KSI-CN probes to a previously determined correlation of IR stretching frequency versus 13 C NMR chemical shift of ethyl thiocyanate in aprotic solvents, such departures can be identified.…”
Section: Tandem Measurement Of Ir Stretch Frequency and 13 C Nmr Chemmentioning
confidence: 89%